Analisis Kinerja SMARTER Pada Sistem Pendukung Keputusan Pemilihan Tukang Las Terbaik Untuk Menerima Penghargaan - Nasib Marbun; Muhammad Zarlis; Rahmad Widya Sembiring (STMIK Budi Darma, 2022)
One of the policies that can be carried out by welding workshop entrepreneurs to maintain the best welders is by giving awards at the beginning of each month to the chosen alternative from the results of decision making by the leadership. The selection of the best welder who is entitled to receive the award can be done with several assessment criteria, including communication skills, knowledge of welding, welding techniques, and teamwork. In order for the decision making to produce good results, of course, a tool is needed in the form of a decision support system. In this study, the SMARTER method was applied in completing the selection of the best welder to receive the award. The results of the analysis of SMARTER's performance in solving the problem of selecting the best welder based on the relative standard deviation, it is known that the accuracy rate is 24%.